Transmission processes of religious knowledge and ritual practice in Alevism between innovation and reconstruction - Zimmermann, Johannes 1977-; Karolewski, Janina 1980-; Langer, Robert 1967- (Frankfurt a.M Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2019)
Knowledge transmission in Alevism – Ritual practice – Written tradition – Oral lore – Scripturalisation – Memory and commemoration – Manuscripts – New media – Mimetics and imitation – Poet-minstrels – Gender roles – Transnational space – Yezidism.
This volume examines transmission processes of Alevi religious knowledge and ritual practice in the last decades. It assembles contributions by researchers from Germany, Great Britain, and Turkey. They focus on the question how religious knowledge and ritual practice are constantly (re-)negotiated and (re-)distributed in Alevism and, as a comparison, in Yezidism. These processes are discussed in regard to the conditions of social and cultural change, transnational migration, and globalised communication. In doing so, the contributions to this volume follow different approaches and discuss fundamental methodological issues
Keywords: Konferenzschrift